Remote Lab Experiments in Mechanic: The Compound Pendulum - Laouina, Zineb; Ouchaouka, Lynda; Moussetad, Mohamed; Mordane, Soumia; Radid, Mohamed (International Journal of Online and Biomedical Engineering (iJOE), 2023)
In the teaching of experimental sciences, practical work plays a crucial role since it allows learners to transfer the knowledge acquired in theoretical courses into practical skills. For this purpose, laboratories allow learning by experience and aim at involving students, which reinforces learning receptivity. Recent years have seen an increasing use of online labs, including both virtual and remote labs, Remote labs, providing online interfaces to physical labs, allow students to conduct experiments with real-world equipment anywhere and at any time. This paper proposes a model of design, development and implementation of a remote manipulation in an E-Lab. It is the compound pendulum which is part of the handling offered to the students of the 1st year of university in the field of physical sciences. The aim of this paper is to make this approach available to allow more experiments on a digital platform in order to allow learning for all, independently of time and place.